Performance of the Environmental and Forestry Office through the 'Zero Waste' Program in Polewali Mandar Regency, West Sulawesi Province - ayu achriany sopian; dwi agus sumarno; Herson simbolon (Utan Kayu Publishing, 2024)
The amount of waste generated in Polewali Mandar Regency in 2022 was 2,852,712 tons from a population of 488,857, indicating that the waste management by the Department of Environment and Forestry, which is responsible for waste issues in Polewali Mandar Regency, is not yet optimal. Meanwhile, Government Regulation No. 97 of 2017 Article 5 paragraph 1 concerning the National Strategy Policy for Household Waste Management and Similar Household Waste targets a waste generation rate of 30%. Therefore, this research aims to identify and describe the performance of the DLHK through the Zero Waste program, the inhibiting factors, and the efforts in waste management in Polewali Mandar Regency. This thesis research uses qualitative descriptive research with an inductive approach. The data collection techniques used by the researcher are interviews, observations, and documentation. The data analysis techniques used in this thesis research consist of data reduction, data presentation, and conclusion drawing or verification. According to Soesilo's theory (Nogi, 2005), the results of this study conclude that in waste management, the performance of the DLHK through the